Exploring the Influence of Demographic Factors on Perceptions of Festival Tourism in Ilara-Mokin, Nigeria: A Social Exchange Analysis - Khidir Bolaji Balogun; Adebimpe Elizabeth Ajagunna (Journal of Tourismology)
This research article explores the influence of demographic factors, including age, gender, income, and education, on residents’ attitudes and perceptions towards festival tourism. A cross-sectional survey design was employed, utilizing purposive sampling, and 400 questionnaires were distributed to festival participants aged 18 and above. Data collection involved a combination of open-ended and closed-ended questions in the questionnaires, with subsequent analysis employing descriptive and inferential statistics. An analysis by gender highlighted disparities between male and female respondents in how they perceived economic impacts, indicating gender-based variations in expectations and perceptions. The female respondents exhibited positive views regarding the economic advantages of festival tourism. In addition, employment type emerged as a significant predictor of perceived social effects, indicating diverse viewpoints among different occupational groups. For festival organizers and tourism operators, the findings underscored the importance of considering the diverse needs and preferences of various demographic groups when designing festival tourism products and services. This approach ensures the maximization of economic benefits while simultaneously balancing social and cultural values. The application of social exchange theory offered valuable insights into the exchange of rewards and costs within festival tourism interactions, influencing perceptions, and behavior.